Metabolomics Analysis in Different Development Stages on SP0 Generation of Rice Seeds After Spaceflight - Zeng, Deyong; Cui, Jie; Yin, YiShu; Xiong, Yi; Liu, Mengyao; Guan, Shuanghong; Cheng, Dayou; Sun, Yeqing; Lu, Weihong (Frontiers in Plant Science, 2021)
Space environment is a special abiotic stress condition. In recent years, it has been confirmed that the space flight caused the stress response of rice seeds, and the protein level, transcription level, and methylation level will change during the planting process after returning to the ground. However, the changes at the metabolome level are not very clear. In this study, two kinds of rice seeds, Dongnong423 (DN3) and Dongnong416 (DN6), were carried on the ShiJian-10 retractable satellite (SJ-10) for 12.5 days in orbit, returned to the ground and planted in the field until the three-leaf (TLP) and tillering stage (TS). The results of antioxidant enzyme activity, soluble sugar, and electron leakage rate revealed that the space environment caused the stress response of rice. The TLP and TS of DN3 identified 110 and 57 different metabolites, respectively, while the TLP and TS of DN6 identified 104 and 74 different metabolites, respectively. These metabolites included amino acids, sugars, fatty acids, organic acids and secondary metabolites. We used qRT-PCR technology to explore the changes of enzyme genes in the tricarboxylic acid cycle (TCA) and amino acid metabolism pathway. Combined with the results of metabolomics, we determined that during the TLP, the TCA cycle rate of DN3 was inhibited and amino acid metabolism was activated, while the TCA cycle rate of DN6 was activated and amino acid metabolism was inhibited. In TS, the TCA cycle rate of DN3 was inhibited, and amino acid metabolism was not significantly changed, while the TCA cycle rate of DN6 was activated and amino acid metabolism was inhibited. These results suggested that the space environment has different stress response mechanisms to the two rice varieties seed, and these differences may be reflected in energy consumption and compound biosynthesis of rice in different growth and development stages. This study provided data support for future research on the mutation mechanism of stable mutants, and provided new insights for further exploring the effects of space biology.